Arts and Culture in Lisbon’s Recent Revitalization : Observing Mouraria and Intendente Square through Alternative Local Initiatives as Drivers of Marginal Gentrification - Ana Estevens; Agustin Cocola-Gant; Daniel Malet Calvo; Filipe Matos (Revue Interventions Économiques)
“Creative cities” and “artistic neighborhoods” have become regular concepts within hegemonic narratives and practices related to centralized urban revitalization processes. Creativity is now sold as a symbol of status and the “creative city” has become a widespread trend common to contemporary cities. At the same time, artists and social movements use art and culture as an instrument of resistance, change and transformation of social relations, implementing in their practices the criticism of the neoliberal city. This paper discusses the links between (i) neoliberal culture-led revitalization strategies; (ii) artists and community groups; and (iii) gentrification. We show that in a free-market context, bottom-up artistic initiatives revalorize areas and the resulting increase in property values are appropriated by private investors, accelerating a process of gentrification.